Peran Guru Kelas Dalam Pelaksanaan Bimbingan Konseling - Wulandari, Emasari; Adiningtiyas, Sri Wahyuni (Jurnal Bimbingan dan Konseling Pandohop, 2023)
Counselling guidance is given in order to overcome the problems that occur in the development process of elementary school age. This study aims to describe the role of class teachers in implementing counselling guidance in personal, social, learning, and career fields at SD Negeri 024 Galang, Batam City. The research used a descriptive research method with a case study approach that describes the implementation of counselling guidance on the research subjects of class teachers I - VI. Primary data were obtained from observations, interviews, and documentation, and tested using triangulation of sources by using the Miles and Huberman model of data analysis techniques which ultimately obtained an overview of the role of class teachers in implementing counselling guidance in the school under study. The results of the study explain that class teachers do not conduct special planning in writing but directly provide guidance services during learning takes place or on certain conditions. Guidance services are carried out in personal, social, learning and career fields. Career guidance is carried out only in high grades (IV - VI) while low grades are not implemented because there is no discussion of ideals or work material.